Supramolecular self-assembled drug delivery system (SADDs) of vancomycin and tocopherol succinate as an antibacterial agent: in vitro, in silico and in vivo evaluations. (20th October 2020) - Salih, Mohammed; Omolo, Calvin A.; Devnarain, Nikita; Elrashedy, Ahmed A.; Mocktar, Chunderika; Soliman, Mahmoud E. S.; Govender, Thirumala
Abstract: In this study self-assembled drug delivery system (SADDs) composed of a hydrophobic d -α-tocopherol succinate (TS) and a hydrophilic vancomycin (VCM) were formulated, and its potential for enhancing the antibacterial activity of VCM against Staphylococcus aureus (SA) and Methicillin-resistant Staphylococcus aureus (MRSA) were explored. The SADDs were synthesized via supramolecular complexation, then characterized for in silico, in vitro and in vivo studies. In silico studies confirmed the self-assembly of VCM/TS into NPs. The size, surface charge and drug loading of the SADDs was ˂100 nm, −27 mV and 68%, respectively. The SADDs were non-hemolytic and biosafe. A sustained release of VCM from SADDs was noted, with 52.2% release after 48 hr. The in vitro antibacterial test showed a twofold decrease in Minimum inhibitory concentration (MIC) against SA and MRSA, and a significantly higher reduction in MRSA biofilms compared to bare VCM. Further, in silico studies confirmed strong and stable binding of TS to MRSA efflux pumps. The in vivo study using mice skin infection models showed a 9.5-fold reduction in bacterial load after treatment with SADDs, in comparison with bare VCM. These findings affirmed that VCM/TS NPs as a promising novel nano-delivery for treating bacterial infections.